Kehamilan Dini Setelah Sleeve Gastrectomy pada Pasien dengan Triple Metabolic Burden: Kasus Kompleks Diabetes Tipe 2, Hipotiroid, dan Preeklampsia Berat dengan Pertumbuhan Janin Terhambat - Amal Bahrum Penas; Cut Meurah Yeni; Yusra Septivera; Cut Rika Maharani; Fara Julyta Aliyah (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Bariatric surgery is effective in treating obesity and type 2 diabetes mellitus (T2DM); however, pregnancy occurring within 12–24 months after surgery carries significant risks. This report presents a complex pregnancy case in a patient with a history of sleeve gastrectomy, post-hemithyroidectomy hypothyroidism, and T2DM. A 29-year-old primigravida conceived 2 months after undergoing sleeve gastrectomy, which successfully induced T2DM remission, with HbA1c decreasing from 11% to 5.5%. Although glycemic control and euthyroid status were maintained throughout pregnancy, the patient developed severe preeclampsia at 35–36 weeks of gestation, complicated by intrauterine growth restriction (IUGR) and oligohydramnios. An emergency cesarean section delivered a male infant weighing 2000 grams with Apgar scores of 8 and 9 at the first and fifth minutes, respectively. The neonate required 14 days of NICU care due to respiratory distress syndrome, respiratory failure, and hyperbilirubinemia. Maternal gestational weight gain was suboptimal at only 4 kg, below the recommended range for pregnant women with obesity. This case highlights the importance of adhering to the recommended surgery-to-conception interval following bariatric surgery. Early pregnancy after surgery, combined with multiple metabolic comorbidities, may contribute to adverse maternal and neonatal outcomes. Multidisciplinary management, comprehensive nutritional monitoring, and optimization of comorbidities before conception are essential to improve pregnancy outcomes in this population.